Alterations of tau and Camk2 in acute stroke and effects of a multicomponent drug - Yue Wu; Rui Zhou; Menglan Wang; Jing Xu; Yi Zhang; Junying Wei; Hongjun Yang (Science of Traditional Chinese Medicine)
Abstract. Background. Stroke is one of the leading causes of death around the world. The sequelae of ischemic stroke cause drastic effects on the quality of life for patients. Sanwujiaowan (SWJW) is a mixture prepared with 5 herbal medicines (Aconiti Lateralis Radix Praeparata, Aconiti Kusnezoffii Radix, Polygoni Multiflori Radix, Aconiti Radix, and Olibanum), with a long history of application in treating the sequelae of stroke. Objectives. To provide evidence and decipher the mechanism of SWJW in alleviating stroke. Materials and Methods. In this article, we expanded the indicators of SWJW by an integrated strategy based on signature metabolomics, target proteins, and bioinformatics and probed into the mechanism of SWJW intervention in ischemic stroke in a rat model. Results. The results indicated that SWJW protected rats from nerve damage during the acute phase of ischemic stroke by regulating tau phosphorylation via the PI3K/Akt pathway. Conclusions. This study, for the first time, proved that the reduction of phosphorylated tau was harmful for the neural function in the acute phase of ischemic stroke. Meanwhile, the pathological changes of phosphorylated tau proteins were detected in stroke and recalled by SWJW. This finding may provide a new reference for formulating treatment strategies for the acute phase of ischemic stroke.